Komunikasi Humas Smk Swasta Imelda Medan Dalam Mempromosikan Sekolah Melalui Media Jurnalistik Dan Media Sosial - Khairunnisari, Wulan; Saragih, M. Yoserizal; ., Zuhriah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Basically, this research aims to determine the forms of communication and media relations barriers carried out by the Public Relations of Medan Imelda Private Vocational School in promoting the school through journalistic media and social media. The research method used in this research is a qualitative method. The informants for this research were the staff and teachers of Medan Imelda Vocational School. The results of the research explain that the journalistic media used by Medan Imelda Private Vocational School in carrying out promotions to welcome new students is Medantalk journalistic media. This form of collaboration is carried out by contacting the admin and asking to post data and activities or school digital brochures on the Medantalk social media news account. Then, the social media that Imelda Medan Private Vocational School also uses to promote welcoming new students is the use of social media accounts, such as Facebook, Instagram and YouTube. The obstacle encountered by SMK Imelda Medan in promoting the school using journalistic media was the slow response from Medantalk in responding to school data sent by SMK Imelda Medan, due to the large number of people using Medantalk's services. Meanwhile, for social media, Public Relations is less active in managing the social media accounts of Imedal Medan Private Vocational School and network problems that often experience disruption or errors, resulting in obstacles in managing social media accounts.